We'll remember the quotient property of
exponentials:
13^(3-x) =
13^3/13^x
We'll re-write the
equation:
13^x - 20 - 13^3/13^x =
0
We'll multiply by 13^x both
sides:
13^2x - 20*13^x - 13^3 =
0
We'll substitute 13^x =
t:
t^2 - 20t - 2197 = 0
We'll
apply quadratic rule:
t1 = [20+sqrt(400 +
8788)]/2
t1 = (20 +
sqrt9188)/2
t1 =
10+sqrt2297
t2 =
10-sqrt2297
13^x =
10+sqrt2297
log 13^x = ln
(10+sqrt2297)
x = log (10+sqrt2297)/ln
13
x = 1.5825 approx.
13^x =
10 - sqrt2297 impossible! ( since 10 < sqrt2297 => 13^x = negative value,
that is impossible).
The equation has only
one solution, x = 1.5825 approx.
No comments:
Post a Comment